(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the degree of coverage of the issues of political, economic and cultural life of Fergana Valley in the works of the world historiography dedicated to the history of the reign of Amir Temur and the Timurids. On the basis of historical sources, the author expresses his attitude to the points of view and reasoning of the historians of the history of the valley.